SOME ISSUES OF ORGANIZING LEASE ACCOUNTING BASED ON INTERNATIONAL FINANCIAL REPORTING STANDARDS - Xasanboyev Okhunjon Khimmatjonovich (European Science Publishing, 2025)
This article analyzes the basis and specific aspects of the organization of lease accounting in accordance with international financial reporting standards. In particular, the differences between the national standard and the international standard, as well as the obstacles and positive aspects of the application of the international standard, are studied, and conclusions are drawn.
Keywords: Lease, IFRS, financial leverage. right-of-use asset, lease liability, lease payments, interest rate, leaseback and sale.